11β-Hydroxylase loss disrupts steroidogenesis and reproductive function in zebrafish. Issue 2 (November 2020) - Oakes, James A; Barnard, Lise; Storbeck, Karl-Heinz; Cunliffe, Vincent T; Krone, Nils P
Abstract : The roles of androgens in male reproductive development and function in zebrafish are poorly understood. To investigate this topic, we employed CRISPR/Cas9 to generate cyp11c1 (11β-hydroxylase) mutant zebrafish lines. Our study confirms recently published findings from a different cyp11c1 −/− mutant zebrafish line, and also reports novel aspects of the phenotype caused by loss of Cyp11c1 function. We report that Cyp11c1-deficient zebrafish display predominantly female secondary sex characteristics, but may possess either ovaries or testes. Moreover, we observed that cyp11c1 −/− mutant male zebrafish are profoundly androgen- and cortisol-deficient. These results provide further evidence that androgens are dispensable for testis formation in zebrafish, as has been demonstrated previously in androgen-deficient and androgen-resistant zebrafish. Herein, we show that the testes of cyp11c1 −/− mutant zebrafish exhibit a disorganised tubular structure; and for the first time demonstrate that the spermatic ducts, which connect the testes to the urogenital orifice, are severely hypoplastic in androgen-deficient zebrafish. Furthermore, we show that spermatogenesis and characteristic breeding behaviours are impaired in cyp11c1 −/ − mutant zebrafish. Expression of nanos2, a type A spermatogonia marker, was significantly increased in the testes of Cyp11c1-deficient zebrafish, whereas expression of markers for later stages of spermatogenesis was significantly decreased. These observations indicate that in zebrafish, production of type A spermatogonia is androgen-independent, but differentiation of type A spermatogonia is an androgen-dependent process. Overall, our results demonstrate that whilst androgens are not required for testis formation, they play important roles in determining secondary sexual characteristics, proper organisation of seminiferous tubules, and differentiation of male germ cells.